Evaluation of Soil Loss by Water in Archaeological Landscapes by Using the (R)USLE Model and GIS. The Case Study of Paphos District, Cyprus - Papageorgiou, Nikoletta; Hadjimitsis, Diofantos G. (My University, 2021)
Soil erosion is one of the most significant environmental issues, as it seriously threatens archaeological sites and monuments. In recent years, several models have been used in the in the relevant scientific literature in order to estimate soil erosion rates. The models range from empirical to physical or process-based and differ significantly in complexity, accuracy, inputs and outputs. Among these, the Revised Universal Soil Loss Equation (RUSLE) has become the most commonly used in different environmental conditions and on varying scales. The present study calculates average annual soil erosion in terms of spatial and temporal patterns based on the Revised Universal Soil Loss Equation (RUSLE) model, combined with Geographic Information Systems (GIS) in the area of Paphos District. This study also implemented satellite remote sensing images and available data sources such as meteorological data, a digital elevation model (DEM), land use and soils maps for soil erosion analysis. The whole methodology is based on the estimation of soil loss per unit area and takes into account specific parameters such as rainfall factor, steepness and slope length factor, cover management, practice factor as well as soil erosion factor. The results indicate that the mean annual soil erosion was estimated from 0 to 235.532 t/ha.
Keywords: Archaeological sites; Remote sensing; RUSLE; Soil erosion